2022
DOI: 10.3390/toxics10100597
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Microplastics during Early Developmental Stage: Review of Current Evidence

Abstract: In the last few decades, microplastics (MPs) have been among the emerging environmental pollutants that have received serious attention from scientists and the general population due to their wide range of potentially harmful effects on living organisms. MPs may originate from primary sources (micro-sized plastics manufactured on purpose) and secondary sources (breakdown of large plastic items through physical, chemical, and biological processes). Consequently, serious concerns are escalating because MPs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…People across the world come into close, daily contact with plastics and the byproducts of their disintegration, especially nano-and microplastics. The discovery of microplastics in the placenta has sparked worries that plastics might affect fetal growth during pregnancy [16,[21][22][23][24][25][26][27][28][29]. Plastic pollution is a serious and growing worldwide issue; by 2060, the amount of plastic that leaks into the environment is expected to have doubled to 44 million tons annually from 22 million tons in 2019 [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People across the world come into close, daily contact with plastics and the byproducts of their disintegration, especially nano-and microplastics. The discovery of microplastics in the placenta has sparked worries that plastics might affect fetal growth during pregnancy [16,[21][22][23][24][25][26][27][28][29]. Plastic pollution is a serious and growing worldwide issue; by 2060, the amount of plastic that leaks into the environment is expected to have doubled to 44 million tons annually from 22 million tons in 2019 [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, maternal exposure to microplastics during breastfeeding and pregnancy altered the neural cell compositions and the histology of the offspring's brains [16,18,20,21]. Studies have shown that exposure to MPs during pregnancy and the first few months of life may result in permanent alterations to the reproductive axis and central nervous system in the offspring of different species [16,21,22]. A lack of evidence has prompted scientists and regulatory bodies to express concerns over the presence of MPs in food, possible human consumption, and potential health effects.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, 4.8–12.7 million tons of plastic litter was deposited into surface waters, and an estimated 100–250 million tons of plastic litter is projected to enter surface waters by 2025. , The ingestion of thousands of plastic particles through inhalation, absorption by the skin, hand-to-mouth behavior by kids playing with plastic toys, from food sources such as plants and fish, and via liquids stored in plastic bottles has become routine, given their widespread societal use. , …”
Section: Introductionmentioning
confidence: 99%
“…7,8 The ingestion of thousands of plastic particles through inhalation, absorption by the skin, hand-to-mouth behavior by kids playing with plastic toys, from food sources such as plants and fish, and via liquids stored in plastic bottles has become routine, given their widespread societal use. 9,10 Studies reveal that MPs' and NPs' buildup is associated with stunted development, hormone disruption, metabolic distortion, oxidative stress, immunological and neurotoxicity malfunction, and genotoxicity. 11,12 Recently, MPs have been detected in 75% of breast milk samples (n = 34 healthy mothers) and in human placentas.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics have been detected in 15 human biological components including breastmilk, bronchoalveolar lavage fluid, blood, lung, liver, kidney, spleen, placenta, meconium, skin, hair, head, face, hand, saliva, colectomy specimens, faeces and sputum [ 8 ]. Babies ingest 553 to 4,550,000 microplastic particles/day through feeding bottles [ 9 ]. This microplastic exposure directly impacts the digestive, reproductive, central nervous, immune and circulatory systems during early developmental stages.…”
Section: Introductionmentioning
confidence: 99%